AGRICULTURAL COMMUNITY TRADITIONS IN BOJONGSARI VILLAGE, NYALINDUNG DISTRICT, SUKABUMI (1986-2024) - Sopiah, Eva; Achmad Hidayat, Asep; Supendi, Usman; Sulasman; Wahyu Hoerudin, Cecep; Najmudi, Salman; Mahfudin Setiawan, Agus (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2025)
This study examines the acculturation of agrarian traditions, particularly the Seren Taun ceremony, in the villages of Bojongsari and Sukamaju, Nyalindung District, Sukabumi, between 1986 and 2024. The Seren Taun ceremony, a harvest celebration, has historically been found in traditional villages such as Kanekes Baduy and Ciptagelar. However, interestingly, this tradition also persists in rural villages such as Bojongsari and Sukamaju, albeit with significant differences due to socio-cultural and religious acculturation. The main objective of this study is to analyze the contents of the traditional “Ririmbon Panen” guidebook found in both villages and to identify the forms of acculturation that influence agricultural practices and religious rituals. Using a qualitative approach, this research involves field methods (observation, interviews, documentation) and philology to edit and translate the texts, supplemented by content analysis to reveal the values contained therein. The results of the study show that the Seren Taun tradition in Bojongsari and Sukamaju, known as “Meteumeuyan,” has undergone profound acculturation with Islamic teachings. This transformation is evident in the replacement of amulets with prayers from the Qur'an and the use of the Islamic calendar in determining harvest times. Although pre-Islamic elements such as offerings and incense burning have been eliminated, other aspects such as calculating auspicious/inauspicious days and wind direction have been retained. In addition, the community still respects Monday as “Nyi Pohaci Day,” when rice processing activities are stopped. The Seren Taun ceremony in these two villages represents a concrete example of cultural acculturation in Indonesian agrarian communities, where indigenous traditions adapt to Islamic thinking, creating a unique blend that enriches cultural meaning without losing its essence. Keywords: Agrarian, Acculturation, Seren Taun, Islam, Sunda.